Qualitative profile of degummed guar (Cyamopsis tetragonoloba L.) seeds grown in a Mediterranean area for use as animal feed. Issue 1 (6th March 2017) - Chiofalo, B.; Lo Presti, V.; D'Agata, A.; Rao, R.; Ceravolo, G.; Gresta, F.
Summary: Guar ( Cyamopsis tetragonoloba L.) is an interesting summer legume multipurpose crop used for the extraction of seed gum, due to its galactomannan content, and the high‐protein by‐product, (germ and hull) used for animal feed. The aim of this study was to assess qualitative traits of degummed seeds, named guar meal, of six guar varieties from India, South Africa and USA, grown in a Mediterranean environment (Sicily, Southern Italy), in order to explore their suitability for livestock, and comparing them with the marketed Indian products of guar meals, Churi and Korma. After harvest, seeds were manually degummed and proximate composition was analysed using the official method of analyses, total phenols and tannins by UV spectrophotometry and fatty acids by GC‐FID. Qualitative profile of degummed guar seeds (DGS) was significantly ( p < .05) influenced by the genotype. Among DGS, Matador showed a high ( p < .05) content of protein (518 g/kg), lipids (59.4 g/kg) and the lowest ( p < .05) NDF level (181 g/kg) compared to the other varieties. Total phenol content of DGS showed similar values among varieties (2.57 mg gallic acid/g, on average) and with those of guar meal Korma 50%–53% (2.89 mg gallic acid/g) and Korma 56%–58% (2.94 mg gallic acid/g). Tannins were below the instrumental limit of quantification (1.5 mg/g of catechin equivalents) in DGS, as well as in the marketed products. Fatty acid composition was significantly influenced ( p < .05) by the genotype. Matador showed the significant highest content of polyunsaturated fatty acids (PUFA) of the n6 series (45.2 g/100 g), whereas India showed the significant ( p < .05) highest content of PUFA of the n3 series (3.55 g/100 g), and the significant ( p < .05) highest level of n3/n6 PUFA ratio (0.08), and the best ( p < .05) Atherogenic Index (0.19) and Thrombogenic Index (0.46). This study shows the interesting nutritional characteristics of degummed guar seeds, underlining that, if the future of the guar gum industries depends largely on the utilization of guar seed meal, this product can be considered a valuable feed resource and a way to increase the income of guar production.